Indigenous stewardship of coastal resources in native California - Sanchez, Gabriel M.; Grone, Michael; Apodaca, Alec (Frontiers in Earth Science, 2023)
Indigenous people have profoundly influenced terrestrial and marine ecosystems by modifying coastal habitats to increase the productivity of target species and altering local biotas through their harvesting practices. In some cases, these actions led to local resource depression, while in other instances, Indigenous people engaged with terrestrial and marine resources in sustainable ways, increasing the resilience of ecosystems. In this paper, we interrogate human-environmental relationships that span the last ~7,000 years of Indigenous engagement with coastal resources on the central California coast. Through a historical ecological framework, we assess how Indigenous peoples interacted with terrestrial and marine ecosystems differently across space and through time. In the Middle Holocene, the region's archaeology is typified by mobile populations using diverse terrestrial and marine resources. By the Late Holocene, Indigenous peoples intensified their economies towards a limited number of marine and terrestrial species. During this time, Indigenous people initiated sustained fire management practices that created habitat mosaics still reflected in the contemporary landscape. In the Late Holocene, people also developed resource harvesting strategies for California mussels and forage fishes geared towards long-term productivity.